EVALUASI PERKULIAHAN MENGGUNAKAN METODE FRAMEWORK PIECES PADA UNIVERSITAS MERCUBUANA - Windu Gata; Nia Kusuma Wardhani (JITK (Jurnal Ilmu Pengetahuan dan Teknologi Komputer), 2017)
Mercubuana University (UMB) is a private university that was getting Higher Education Accreditation (Akreditasi Institusi Perguruan Tinggi - AIPT) with an A in 2016. UMB has implemented E-learning since 2009 in all faculties. E-learning users, such as students and professors, can use an E-Learning Mercubuana University for 24 (twenty four) hours with a range of facilities as well as the use of Single Sign-On for login. Facilities at E-Learning are the Dashboard, Course Overview, Forum, Quiz, Assignment, and others. In this research, The questionnaire was designed using the PIECES framework modified and distributed to 23 lectures and 23 students related to college the first semester of 2016-2017 with a sample random sampling method. The result of Implementation of online courses at the University Mercubuana Agree that there is value in Performance (67%), Information (61.7%), Economic (79.37%), Control (61.61%), and Service (61.97%). As for the assessment in the implementation Eficiency to E-Learning is Strongly Agree (80.81%).